2020
DOI: 10.1177/2325967120967120
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Tears: The Impact of Increased Time From Injury to Surgery on Intra-articular Lesions

Abstract: Background: Previous research has shown that meniscal and articular cartilage lesions increase with time in the anterior cruciate ligament (ACL)–deficient knee. Purpose: To analyze the association between increased time from ACL injury to reconstruction and the presence of intra-articular lesions. Design: Cross-sectional study; Level of evidence, 3. Methods: A retrospective chart review was performed for patients who sustained an ACL injury and underwent reconstruction from January 1, 2009, to May 14, 2015. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…ACL tears usually accompany meniscus injuries, but no studies have researched the different types of ACL tears that may influence the prevalence of meniscus tears or different meniscus tear types. In this study, the total prevalence of a meniscus tear with an ACL tear was 56.0%, similar to that in existing research, which has been reported to be 51.9–73.0% [10, 11, 15, 34, 38]. The prevalence [15/22 (68.2%)] of a medial meniscus tear with type I injury was higher than that of other types.…”
Section: Discussionsupporting
confidence: 88%
“…ACL tears usually accompany meniscus injuries, but no studies have researched the different types of ACL tears that may influence the prevalence of meniscus tears or different meniscus tear types. In this study, the total prevalence of a meniscus tear with an ACL tear was 56.0%, similar to that in existing research, which has been reported to be 51.9–73.0% [10, 11, 15, 34, 38]. The prevalence [15/22 (68.2%)] of a medial meniscus tear with type I injury was higher than that of other types.…”
Section: Discussionsupporting
confidence: 88%
“…We identified an almost 25% decrease in probability of meniscal survivorship with an increase in the time to receive surgical intervention beyond 100 days, confirming the findings of extensive previous investigations. 7,22,42 Everhart et al 12 specifically identified delay in ACLR of 8 weeks as the threshold beyond which the risk for a secondary medial meniscal tear identified at time of surgery became significant; similarly, we observed that time to surgery between 50 and 60 days corresponded to the global minima in meniscal survivorship. Interestingly, one modifiable predictor identified in the ACLR model was the use of an expansion device for tibial fixation; although a prospective evaluation noted no clinical differences between methods of fixation for soft tissue grafts at short-term follow-up, 18 this finding may prompt surgeon discretion when choosing this alternative compared with direct compression and suspensory fixation.…”
Section: Discussionsupporting
confidence: 72%
“…In regards to time to ACL reconstruction and associated meniscus tear, a retrospective analysis of West Point cadets undergoing ACL reconstruction showed a 39% incidence of associated meniscus tears and no difference in tear repairability in patients undergoing acute reconstruction (within 30 d) or later reconstruction 54. This is in contrast to studies in the pediatric population that show a significantly higher rate of medial meniscus tears if ACL reconstruction is delayed between 3 and 6 months 35,55,56…”
Section: Concomitant Injuries and Conditionsmentioning
confidence: 91%
“…54 This is in contrast to studies in the pediatric population that show a significantly higher rate of medial meniscus tears if ACL reconstruction is delayed between 3 and 6 months. 35,55,56…”
Section: Ligament Injurymentioning
confidence: 99%